2015
DOI: 10.1097/aap.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

The Second ASRA Practice Advisory on Neurologic Complications Associated With Regional Anesthesia and Pain Medicine

Abstract: The Second American Society of Regional Anesthesia and Pain Medicine Practice Advisory on Neurologic Complications Associated With Regional Anesthesia and Pain Medicine updates information that was originally presented at the Society's first open forum on this subject (2005) and published in 2008. Portions of the second advisory were presented in an open forum (2012) and are herein updated, with attention to those topics subject to evolving knowledge since the first and second advisory conferences. The second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
254
2
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(272 citation statements)
references
References 191 publications
(193 reference statements)
2
254
2
14
Order By: Relevance
“…There is no evidence for or an established role of DOAC monitoring to improve clinical outcomes in periprocedural settings. Finally, special care regarding these timelines for DOACs should also be taken in patients undergoing neuraxial anesthesia [51].…”
Section: The Perioperative Anticoagulant Use For Surgery Evaluation (mentioning
confidence: 99%
“…There is no evidence for or an established role of DOAC monitoring to improve clinical outcomes in periprocedural settings. Finally, special care regarding these timelines for DOACs should also be taken in patients undergoing neuraxial anesthesia [51].…”
Section: The Perioperative Anticoagulant Use For Surgery Evaluation (mentioning
confidence: 99%
“…Lubrano et al [11] demonstrated a transient tubular dysfunction after induced hypotension with propofol and remifentanil (without concurrent adrenaline); however, a clear link to permanent renal dysfunction has not been demonstrated [17]. Specific concerns regarding spinal cord ischemia caused by prolonged periods of hypotension with neuraxial anesthetics is also well documented; studies have demonstrated a MAP of at least 60 mmHg is required to safely maintain spinal cord blood flow [14]. It must be stressed that these studies have reviewed standard neuraxial anesthesia with uncontrolled hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Studies mentioned that the risk of spinal haematoma is higher with epidural anaesthesia compared to spinal anaesthesia [57]. The risk is higher in patients who have coagulation abnormalities, advanced age, female gender, concurrent spinal stenosis or preexisting neurological diseases [58].…”
Section: Anaesthesia and Peripheral Nerve Injurymentioning
confidence: 99%
“…Studies mentioned that the risk of spinal haematoma is higher with epidural anaesthesia compared to spinal anaesthesia [57]. The risk is higher in patients who have coagulation abnormalities, advanced age, female gender, concurrent spinal stenosis or preexisting neurological diseases [58].Improper positioning is another cause of anaesthesia-related perioperative peripheral nerve injury. Wrong patient positioning increases the compression pressure on nerves which are superficial or in close proximity to a bone.…”
mentioning
confidence: 99%